KEEPING HALAL SUBSTANCE IN THE MIDDLE OF COMPETITION OF HALAL INVESTIGATION INSTITUTIONS AND SELF DECLARE PATHWAY IN INDONESIA - Moch. Khoirul Anwar; A'rasy Fahrullah; Moh. Farih Fahmi; Ahmad Ajib Ridlwan (AMWALUNA (Jurnal Ekonomi dan Keuangan Syariah), 2022)
Halal and haram is a matter of principle in Islamic teachings, because it is not just ta'aqquli but also ta'abbudi. On the other hand, the emergence of many Halal Inspection Agencies (LPH) allows competition to arise between them by providing the best service for business actors. In addition, the Government is also highly promoting halal certification through the self-declare route. If you are not careful, then this can threaten the halal substance. This paper is included in the category of conceptual or library research ( Library Research ) whose research focus will be directed at various literatures that discuss halal substances and policies regarding halal inspection. Furthermore, the data was analyzed using Content Analysis in framework identify characteristics Specific message or data that has been collected. Result of study This show that in order to maintain halal substance, Halal Inspection Agency and Halal Assistance should not only be profit oriented but also oriented towards protecting Muslim consumers. Second, the Ministry of Religion of the Republic of Indonesia must play an active role in regulating and providing guidance to the Halal Inspection Agency and Halal Companion. Third, Halal Auditor and Halal Companion as representatives of the clergy must uphold honesty and be free of conflicts of interest. Fourth, among members of the MUI fatwa commission that determines product halalness, there must be someone who understands food technology or the like.